Geographical variation in high-impact chronic pain and psychological associations at the regional level: a multilevel analysis of a large-scale internet-based cross-sectional survey - Wakaizumi, Kenta; Tanaka, Chisato; Shinohara, Yuta; Wu, Yihuan; Takaoka, Saki; Kawate, Morihiko; Oka, Hiroyuki; Matsudaira, Ko (Frontiers in Public Health, 2024)
BackgroundA geographical analysis could be employed to uncover social risk factors and interventions linked to chronic pain. Nonetheless, geographical variation in chronic pain across different regions of Japan have not been well explored. This study aims to investigate geographical variation in high-impact chronic pain (HICP), defined as moderate to severe chronic pain, and examine the associated psychological factors at the prefecture level.MethodsA cross-sectional Internet-based survey involving 52,353 participants was conducted to assess chronic pain conditions, stress levels, mood states, educational levels, living status, regions, sleep duration, and exercise habits. A geographical analysis evaluated the prevalence of HICP at the prefecture level, and a multilevel analysis explored the risk factors for HICP at both individual and prefecture levels.ResultsThe geographical analysis revealed that Fukushima exhibited the highest HICP prevalence (23.2%; z-score = 2.11), Oita ranked second (23.0%; z-score = 2.00), and Okinawa showed the lowest prevalence (14.9%; z-score = −2.45). Geographical maps of Japan indicated that regional-level subjective stress, negative emotions, and short sleep were associated with higher HICP prevalence. In contrast, positive emotions, such as vigor, were associated with lower prevalence. Multilevel analysis revealed a significant improvement in model fit after incorporating psychological factors at the prefecture level (p < 0.001) and identified significant associations between high subjective stress and low vigor at the prefecture level with HICP prevalence (p < 0.001).ConclusionThere are regional differences in HICP prevalence, and at the prefecture level, subjective stress and vigor are associated with HICP.